Device Engineering of organic field effect transistors for sensing applications - Dey, Anamika (My University, 2017)
Considering the demand of future technology, the thesis entitled “Device Engineering of Organic Field Effect Transistors for Sensing Applications” introduces important methodologies which have been developed for improving the performances of OFET. The thesis mainly focuses to modify the gate dielectric layer to reduce the operational voltage of both p-type and n-type OFETs and use them for various sensing applications. By modulating gate dielectric layer with the combinations of a high-k inorganic and two low-k organic dielectric materials, the operational voltage of OFET was effectively reduced from 50 V to 7 V, which was later used for photo-sensing application. Again, by using the combination of two inorganic and one organic dielectric material layer, the operational voltage of OFET was further successfully reduced from 7 V to 2 V and the same device architecture was used for bio-sensing application. This thesis mainly described very simple, unique and robust methodologies for lowering the operational voltage of OFETs up to 2 V, which can be further used as very effective and stable platforms in the next generation of portable electronics.
Iyer, Parameswar Krishnan
Keywords: Organic Semiconductors; OFETs; PS-OFETs; Biosensors; Dielectric Materials; Operational Voltage